2008
DOI: 10.1074/jbc.m803077200
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90-mediated Assembly of the 26 S Proteasome Is Involved in Major Histocompatibility Complex Class I Antigen Processing

Abstract: Heat shock protein 90 (hsp90) and the proteasome activator PA28 stimulate major histocompatibility complex (MHC) class I antigen processing. It is unknown whether hsp90 influences the proteasome activity to produce T cell epitopes, although association of PA28 with the 20 S proteasome stimulates the enzyme activity. Here, we show that hsp90 is essential in assembly of the 26 S proteasome and as a result, is involved in epitope production. Addition of recombinant hsp90␣ to cell lysate enhanced chymotrypsinlike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 22 publications
2
23
0
1
Order By: Relevance
“…Heat shock protein 90 (HSP90) has been suggested to play a role in the endogenous MHC I antigen processing pathway (12)(13)(14)(15). HSP90 associates with peptides as postproteasomal degradation products (14) or with newly synthesized polypeptides destined for degradation by the proteasome (13).…”
mentioning
confidence: 99%
“…Heat shock protein 90 (HSP90) has been suggested to play a role in the endogenous MHC I antigen processing pathway (12)(13)(14)(15). HSP90 associates with peptides as postproteasomal degradation products (14) or with newly synthesized polypeptides destined for degradation by the proteasome (13).…”
mentioning
confidence: 99%
“…For the first time, we ap- plied this method directly on WT and ECM29 deficient mice liver and identified Hsp90 by MS. In mammalian cells, only one study discussed the involvement of Hsp90 in the proteasome assembly in vitro [37]. In yeast, previous studies [35] [36] revealed an interaction between the proteasome and Hsp90.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90α is inducible under stress conditions, while Hsp90β is constitutively expressed. Recent studies mainly in yeast also implied that Hsp90 is involved in the maintenance of the 26S structure of the proteasome [35]- [37].…”
Section: Introductionmentioning
confidence: 99%
“…Among the putative functions of HSP90, some of which are achieved along with its partners (the HSP70-HSP90 system, and/or co-chaperone p23), 51 HSP90 may participate in the "extraction" of soluble ERAD substrates from the ER lumen to the cytosol. 52 It may further contribute to the assembly and integrity of the 26S proteasome 53,54 and to directing misfolded proteins to the ubiquitin-proteasome degradation pathway. 40 One of the known effects of celastrol is an inhibition of the expression of the gene encoding this protein.…”
Section: Discussionmentioning
confidence: 99%